2014
DOI: 10.1186/1477-3155-12-2
|View full text |Cite
|
Sign up to set email alerts
|

Antibiofilm properties of chemically synthesized silver nanoparticles found against Pseudomonas aeruginosa

Abstract: Nanomedicine is now being introduced as a recent trend in the field of medicine. It has been documented that metal nanoparticles have antimicrobial effects for bacteria, fungi and viruses. Recent advances in technology has revived the use of silver nanoparticles in the medical field; treatment, diagnosis, monitoring and control of disease. It has been used since ancient times for treating wide range of illnesses. Bacterial cells adheres to surfaces and develop structures known as biofilms. These structures are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
78
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(91 citation statements)
references
References 18 publications
6
78
0
Order By: Relevance
“…Multidrug resistant (MDR) strains of P. aeruginosa were treated with AgNPs to investigate the eventual increased resistance compared to sensible strains. In the multidrug resistant strains, the inhibition rate of AgNPs was highest at concentration of 20 μg/mL similarly to the parental strain, therefore biofilms derived from multiresistant bacteria do no show an increased resistance to silver [69].…”
Section: Agnps Antibiofilm Activitymentioning
confidence: 98%
“…Multidrug resistant (MDR) strains of P. aeruginosa were treated with AgNPs to investigate the eventual increased resistance compared to sensible strains. In the multidrug resistant strains, the inhibition rate of AgNPs was highest at concentration of 20 μg/mL similarly to the parental strain, therefore biofilms derived from multiresistant bacteria do no show an increased resistance to silver [69].…”
Section: Agnps Antibiofilm Activitymentioning
confidence: 98%
“…Palanisamy et al tested silver nanoparticles (2.5, 5, 10 and 20 µg/mL) against bacterial growth and reported that multidrug-resistant bacteria were more sensitive to AgNPs at 20 µg/mL [27]. Additionally Wilding et al reported that the oral administration of AgNPs at 1 mg/mL and 10 µL/g of body mass, in repeated doses during 28 days, do not cause a significant effect on the murine gut microbiome [7].…”
Section: Antibacterial Activity Of the Silver Nanocompositementioning
confidence: 99%
“…The penetration rate of the biofilm may also differ between strains. The ability of silver nanoparticles to agglomerate may also have meaning to their the activity [17]. Therefore, Nookola et al [19] demonstrated antibacterial and antifungal properties of chemical silver nanoparticles on environmental strains.…”
Section: Antibacterial Activity Of Chem-and Bio-agnpsmentioning
confidence: 99%
“…Nanoparticles have specific properties and chemical reactivity [6,17,19]. One of them is high surface area to volume.…”
Section: Introductionmentioning
confidence: 99%